Cashless payments and economic growth: Evidence from selected OECD countries - Teck-Lee Wong; Wee-Yeap Lau; Tien-Ming Yip (Journal of Central Banking Theory and Practice, 2020)
This study investigates the relationship between cashless payments and economic growth in selected OECD countries. Using annual data from 2007 to 2016, our results indicate that: Firstly, cashless payment stimulates economic growth in OECD countries. Specifically, the growth-enhancing effect is found in debit card payment while credit card, e-money and cheque payment have no impact on economic growth; Secondly, the positive relationship between economic growth and debit card payment is robust after controlling for the effect of endogeneity, omitted variable bias and outliers. Based on the findings, this study offers some imperative policy recommendations.
Keywords: G20; G21; G23; 330; Cashless payments; Economic growth; Organisation for Economic Co-operation and Development (OECD); debit card payment